Rancang Bangun Thermohygrometer dengan Sensor Pemantauan Gas Medik Berbasis Internet Of Things (IoT) - Setyo Adi Nugroho; Yuli Siyamto; Fitri Anindyahadi; Mahardira Dewantara (Jurnal Ilmiah Dan Karya Mahasiswa, 2025)
A thermohygrometer is a device used to measure temperature, humidity, and the concentration of medical gases (CO and CO₂) in operating rooms. The temperature in an operating room should be maintained between 19°C and 24°C, and humidity between 45% and 65%, to prevent damage to electronic equipment and corrosion caused by low temperatures and high humidity. Medical gases containing oxygen can also accelerate corrosion. Therefore, a thermohygrometer equipped with medical gas readings is necessary. This study aims to design a thermohygrometer using a DHT22 sensor to measure temperature and humidity and an MQ-135 sensor to detect CO and CO₂ gases. The obtained data is displayed on an I2C LCD screen and sent to the Blynk application via WiFi using an ESP32. Testing shows a temperature reading error of -0.02%, humidity -0.02%, CO gas 0.32%, and CO₂ -0.16%, all within a tolerance limit of ±5%.